Study of the didactic – mathematical knowledge of a university teacher: a theoretical framework of research (2015)
This article describes the elements that constitute the theoretical framework to answer the research question: what basic and mathematic knowledge need the students of mathematical training of a group object suitable teaching? The term didactic suitability is defined in the theoretical framework of the Ontosemiotic approach of the Knowledge and Mathematical Instruction – EOS, and it is referred to the identification of potential improvements of the process of study which increase this didactic suitability. The Epistemic phase is referred to the mathematical knowledge of the teacher about the mathematical content, like an institutional order whose teaching is planned, implemented and evaluated. The epistemic dimension belongs to one of the components in the model of didactic -mathematical knowledge - CDM, defined in the EOS which is a theoretical framework of research in the Didactics of Mathematics.